Rethinking globalisation. - Davis, Jim (Race & Class)
Part of a special issue on the threat of globalism. The writer offers an alternative approach to the idea of globalization. He argues that “globalization” is simply a generic term for a number of different processes under way today and that it cannot be understood in isolation from its underlying technological basis. Globalization has only been made possible by the emergence of new technologies; thus, a discussion of globalization is essentially a discussion of new technologies, their relationship to capitalism, and the possibilities they create. This perspective does not claim that capitalism no longer operates according to the laws of the past, but it recognizes that what is taking place today is new, epochal, and different from the capitalism of previous eras.